Political economy of urban settlement demolitions and state power in Zimbabwe: a case study of Harare Metropolitan Province since 2013 - Mhlanga, Kowanai (University of the Free State, 2022)
After the enactment of the Constitution in 2013, which prohibits arbitrary eviction, urban settlement demolitions resumed and escalated in Zimbabwe. This thesis examined the political economy of urban settlement demolitions and state power in Zimbabwe, to assess the extent to which the new Constitution, adopted in 2013, has transformed the conduct of urban settlement demolitions in Harare Metropolitan Province since then. If there is transformation, the thesis sought to understand how the opposition-party-led local authorities have been able to alter the nature of urban settlement demolitions. If there is no transformation, the thesis sought to expose the bottlenecks or restrictive underlying conditions that have curtailed the transformation in the conduct of urban settlement demolitions. It also sought to highlight the consequences of such transformation, or lack thereof, for the State. The political economy approach, the Actor-Network Theory (ANT), and the Procedural Social Justice Theory informed this study. Guided by the constructivist paradigm, the study adopted qualitative methodology. Purposive sampling was employed to select study sites, participants from the state sector and some from the non-state sector. Snowball sampling was employed to choose evictees and other participants from the non-state sector. Convenient sampling was used to select people who witnessed demolitions. Court judgements and newspaper articles on evictions complemented the primary findings. Whilst the study was based on the premise that Zimbabwe's Constitution which was adopted in 2013 is transformative on matters of urban settlement demolition, the research outcomes show that these constitutional changes have not in any way transformed the conduct of demolitions. The research outcomes revealed that up to 2020, demolition of illegal settlement occurred in violation of the canons of Zimbabwe's declaration of rights. First, demolitions occurred without the court authorisation. Second, they were conducted without any consideration of all relevant circumstances. However, such violation of the eviction law taints the image and reputation of the State. Legal, behavioural and institutional factors were found to be the main bottlenecks that have inhibited the transformation. The study found that the 2013 Constitution is still based on the Roman-Dutch law, which is hostile to the plight of illegal land occupiers. Hence, these vestiges of colonial planning legislation do not provide for fair compensation to anyone deprived of property during the councils' operationalisation of the master plan. Regarding behavioural factors, the study found that besides councils' resistance to embracing Section 74, the citizens’ adversarial action towards the governmentality of urban space has impeded transformation. The study recommends that citizens should respect the administrative authorities 'governmentality of the urban space. It also recommends that since Section 74 is the blueprint on matters of evictions, the judiciary which is the guarantor of this Section, should strongly penalize officials who violate this eviction procedure. As a contribution to knowledge production, the study brought new approaches to the investigation of urban settlement demolitions. First, these demolitions have been investigated from the constitutional perspective. This is a departure from the planning perspective that has dominated debates on evictions. No planning law should supersede the Constitution. Second, the ANT has been used to analyse the demolitions. The approach showed the contribution of a multiplicity of players. It revealed how the illegal settlers’ counter-conduct has been exploited by authorities to justify the use of force. Another contribution is the enhancement of S74 as the new eviction framework. The study reveals that this framework can further be strengthened through stakeholder participation and prosecuting its violators. Regarding stakeholder participation, the thesis demonstrates how the Parliamentary Portfolio Committee can use citizens' voices to devise an Act that defines relevant circumstances the court should consider before granting an eviction order.
Dissertation (M.Sc.(Geology))--University of the Free State, 2022
Keywords: Demolitions; Urban settlements; Political economy; Harare Metropolitan Province; Transformation; Constitution; State power; Section 74